The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00345-019-02936-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of T1 substaging on oncological outcomes in patients with non-muscle-invasive bladder urothelial carcinoma: a systematic literature review and meta-analysis

Abstract: Purpose To evaluate the prognostic value of substaging on oncological outcomes in patients with T (or pT1) urothelial carcinoma of the bladder. Methods A literature search using PubMed, Scopus, Web of Science, and Cochrane Library was conducted on March 2019 to identify relevant studies according to the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) guidelines. The pooled disease recurrence (DR) and disease progression (DP) rate in T1(or pT1) patients were calculated using a fixed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…Few studies have evaluated the relationship between the FGFR4 polymorphism and the tumor severity of UCC. In the current study, both the SNP rs2011077 and SNP rs1966265 elevated the risk of UCC progression concerning the tumor stage, tumor size, and the histopathologic grading, while the T status is significantly correlated to the oncological outcome of UCC [40][41][42]. To our knowledge, this is a preliminary experience to find an unrevealed genetic risk factor of progression and prognosis in those with UCC.…”
Section: Discussionsupporting
confidence: 46%
“…Few studies have evaluated the relationship between the FGFR4 polymorphism and the tumor severity of UCC. In the current study, both the SNP rs2011077 and SNP rs1966265 elevated the risk of UCC progression concerning the tumor stage, tumor size, and the histopathologic grading, while the T status is significantly correlated to the oncological outcome of UCC [40][41][42]. To our knowledge, this is a preliminary experience to find an unrevealed genetic risk factor of progression and prognosis in those with UCC.…”
Section: Discussionsupporting
confidence: 46%
“…Since fewer T1G3/HG tumors with CIS are located in the prostatic urethra, and the debate on treatment mainly focuses on the primary T1G3 tumors, we only analyzed the remaining five risk factors in the definition of highest‐risk tumor: concurrent CIS, multiple, large, some form of VH and LVI. In recent years, studies have shown that T1 substaging and molecular typing are related to tumor prognosis, which can enable us to select patients with poor prognosis 20,21 . However, they were not included in the criteria for highest‐risk tumor in guidelines, so they were not analyzed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that tumor depth invasion of the muscolaris mucosae as well as extensive or multifocal invasion of the lamina propria could be such a feature for patients with T1 BCa. A recent meta-analysis evaluated the prognostic value of the subcategorization of oncological outcomes in patients with T1 BCa ( 8 ). The prognostic value of pT1 substaging on at least one oncological outcome was established in 29 studies.…”
Section: Discussionmentioning
confidence: 99%
“…This was done according to the location of the invasion: above the muscularis mucosa–vascular plexus (MM-VP) (T1 a ), in the MM-VP (T1 b ), or beyond the MM-VP (T1 c ). A recent meta-analysis demonstrated a worse prognosis for T1 tumors with deep MM invasion ( 8 ). However, other studies underlined that the substaging of T1 BCa is technically difficult because MM and VP represent inconsistent histologic landmarks for staging (i.e., not always present).…”
Section: Introductionmentioning
confidence: 99%